Isolation and Characterization of Flowers of Rosa damascena - PARIDHAVI, M.; AGRAWAL, S.S. (Asian Journal of Chemistry, 2010)
In the present study, three compounds were isolated and characterized from ethyl acetate fraction of alcoholic extract of the flowers of Rosa damascena. The compounds cedr-6-en-12-ol-14-oic acid, n-cosan-5β-ol and 7-hydroxy-4-(3'-methyl butanoxyl)coumarin-3-en-2-one were reported.